A little good is good enough: Ethical consumption, cheap excuses, and moral self-licensing - Jannis Engel; Nora Szech (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2017)
This paper explores the role of cheap excuses in product choice. If a product improves upon one ethically relevant dimension, agents may care less about other independent ethical facets of the product. Opting for a product that fulfills one ethical aspect may thus suffice for keeping a high moral self-image in agents, and render it easier to ignore other ethically relevant aspects they would otherwise care about. The use of such cheap excuses could thus lead to a 'static moral self-licensing' effect. This would extend the logic of the well-known moral self-licensing over time. Our experimental study provides empirical evidence that the static counterpart of moral self-licensing exists. Furthermore, effects spill over to unrelated, ethically relevant contexts later in time. Thus, static moral self-licensing and moral self-licensing over time can amplify each other. Outsiders, though monetarily incentivized for correct estimates, are completely oblivious to the effects of moral selflicensing, both, static and over time.
urn:nbn:de:swb:90-685139
Keywords: D03; D84; 330; moral self-licensing; moral spillovers; cheap excuses; outsider beliefs; moral personality